Effect of Management Practices on Soil Microstructure and Surface Microrelief - R. Garcia Moreno; T. Burykin; M. C. Diaz Alvarez; J. W. Crawford (Applied and Environmental Soil Science)
Soil surface roughness (SSR) and porosity were evaluated from soils located in two farms belonging to the Plant Breeding Institute of the University of Sidney. The sites differ in their soil management practices; the first site (PBI) was strip-tilled during early fall (May 2010), and the second site (JBP) was under power harrowed tillage at the end of July 2010. Both sites were sampled in mid-August. At each location, SSR was measured for three 1 m2 subplots using shadow analysis. To evaluate porosity and aggregation, soil samples were scanned using X-ray computed tomography with 5 μm resolution. The results show a strong negative correlation between SSR and porosity, 20.13% SSR and 41.38% porosity at PBI versus 42.00% SSR and 18.35% porosity at JBP. However, soil images show that when soil surface roughness is higher due to conservation and soil management practices, the processes of macroaggregation and structural porosity are enhanced. Further research must be conducted on SSR and porosity in different types of soils, as they provide complementary information on the evaluation of soil erosion susceptibility.